1998
DOI: 10.1364/ao.37.004663
|View full text |Cite
|
Sign up to set email alerts
|

Low-order adaptive deformable mirror

Abstract: We report the main parameters of a nine-electrode bimorph piezoelectric adaptive mirror designed to correct low-order aberrations. We describe measurements of the control coefficients for defocus, astigmatism, pure coma, and spherical aberration of this mirror and the temperature stability of its profile. The performance of a simple adaptive optical system for imaging through laboratory-generated turbulence is investigated. This low-order device is suitable for small (<1-m-diameter) telescopes and for nonastro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(34 citation statements)
references
References 14 publications
0
34
0
Order By: Relevance
“…et al 17 ) additional external beam-shaping optics, a wavefront sensor and an optimization routine to iterate towards the desired phase profile. There have also been attempts at dynamic intra-cavity beam control with deformable mirrors [18][19][20][21][22][23] , but such elements have very limited stroke, are limited in the phase profiles that can be accommodated 18,19 , and thus have found little application in laser mode shaping. Rather, such mirrors have been instrumental in high-power applications such as correcting mode distortions (for example, because of thermal load) or in maximizing energy extraction and optimization of laser brightness [20][21][22][23] .…”
mentioning
confidence: 99%
“…et al 17 ) additional external beam-shaping optics, a wavefront sensor and an optimization routine to iterate towards the desired phase profile. There have also been attempts at dynamic intra-cavity beam control with deformable mirrors [18][19][20][21][22][23] , but such elements have very limited stroke, are limited in the phase profiles that can be accommodated 18,19 , and thus have found little application in laser mode shaping. Rather, such mirrors have been instrumental in high-power applications such as correcting mode distortions (for example, because of thermal load) or in maximizing energy extraction and optimization of laser brightness [20][21][22][23] .…”
mentioning
confidence: 99%
“…24 Other measurements reveal a change of 0.34 μm°C −1 due to defocus upon homogeneous loading between 17°C and 23°C and a glass substrate. 25 A mirror with Pyrex substrate shows a P-V deformation of −0.12 μm°C −1 over a temperature range of 30°C to 45°C. 16 All the relevant previous studies have reported that defocus is the major component under homogeneous loading.…”
Section: Homogeneous Loadingmentioning
confidence: 99%
“…Controlling transverse modes in a laser cavity is a difficult task experimentally, usually employing custom optical elements [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] in the form of diffractive and/or aspheric optics, adaptive mirrors or graded phase mirrors, or specialized apertures. Good beam quality associated with lower-order modes is a fundamental requirement for most laser applications.…”
Section: Introductionmentioning
confidence: 99%